On the solutions of the heat, wave and Laplace equations with nonlocal conditions - Babatin, Mohammed (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
In this paper, we present a new approach to solve nonlocal initial- boundary value problems for heat, wave and Laplace equations subject to initial, final and nonlocal boundary conditions of integral type. We first transform the given nonlocal initial-boundary value problems of integral type and then apply the method of separation of variables.